Christian Higher Education : faith, teaching, and learning in the evangelical tradition - Dockery, David S.; Morgan, Christopher W., 1971- (Wheaton, Illinois : Crossway, 2018)
Almost all higher education at one point in history was considered Christian higher education. But many institutions have drifted away from their Christian heritage, supplanting it with myriad alternative worldviews. Committed to developing serious Christian thinkers and scholars, 29 experts from a wide variety of disciplines and institutions have come together to offer a renewed vision for the distinctive work of Christian higher education. Explaining the foundational beliefs about God, knowledge, and humanity that underlie Christian higher education, this volume demonstrates how the Christian tradition shapes approaches to teaching, learning, scholarship, and practice. A deeper understanding of this vision will equip Christian teachers and students to more effectively engage the broader culture and lead both church and society, for the good of the world and the glory of God. --
Preface -- Part 1: The Theological Shape of Christian Higher Education in the Evangelical Tradition : Christian Higher Education: An Introduction / David S. Dockery -- Knowing And Loving God: Toward A Theology of Christian Higher Education / Nathan A. Finn -- The Authority of Holy Scripture: Commitments for Christian Higher Education in the Evangelical Tradition / John D. Woodbridge -- The Study of Holy Scripture and the Work of Christian Higher Education / George H. Guthrie -- Made in the Image of God: Implications for Teaching and Learning / John F. Kilner -- Foundations of Christian Higher Education: Learning from Church History / Bradley J. Gundlach -- Part 2: Faith, Teaching, and Learning in the Evangelical Tradition : The Christian Worldview for Faith, Teaching, and Learning in the Evangelical Tradition / Christopher W. Morgan -- Faith and Teaching / Donald C. Guthrie -- Faith and Learning / Laurie R. Matthias -- The Importance of Research for Teaching and Learning / David W. Pao and Chrystal L. Ho Pao -- Teaching and Learning in the Humanities / Gene C. Fant Jr. -- Teaching and Learning in the Sciences / Glenn A. Marsch -- Teaching and Learning in Mathematics / Paul R. Bialek -- Teaching and Learning in the Social Sciences / Eric L. Johnson and Russell D. Kosits -- Teaching and Learning in Philosophy / Chris L. Firestone -- Teaching and Learning in Music and the Arts / Don P. Hedges -- Teaching and Learning in Education / Karen A. Wrobbel -- Teaching and Learning in Adult and Professional Programs / Timothy L. Smith -- Part 3: Faith, Teaching, and Learning: Applications and Implications for the Campus, the Church, the Marketplace, and the World : Faith, Learning, and Catechesis / S. Steve Kang Faith, Learning, Worship, and Service / Taylor B. Worley -- Faith, Learning, and Living / Felix Theonugraha -- Teaching, Learning, and Leadership / Katherine M. Jeffery -- Faith, Learning, and the World / Greg Forster -- Faith, Ethics, and Culture / Micah J. Watson -- Faith, Teaching, and Learning in Service to the Church / Thomas H. L. Cornman -- The Importance of Intercultural and International Approaches in Christian Higher Education / Peter T. Cha -- Missions, the Global Church, and Christian Higher Education / Bruce Riley Ashford.
Includes bibliographical references and indexes.
Keywords: Education (Christian theology); Evangelicalism; Christian universities and colleges; Theological seminaries; Education, Higher; Postsecondary education